Structures and photocatalytic activity of α-Fe2O3@TiO2 core - shell nanoparticles. (1st April 2022) - Niu, Yongan; Li, Manyuan; Jia, Xueyan; Shi, Zihang; Liu, Haixiong; Zhang, Xin
Abstract: We successfully fabricated the ellipsoidal α-Fe2 O3 @TiO2 nanoparticles (NPs) by modified Stöber method and 3D flower-like α-Fe2 O3 @TiO2 NPs by solvothermal method, using tetrabutyl titanate (TBOT) as the titanium precursor. These as-obtained α-Fe2 O3 @TiO2 NPs were calcined at 500 °C, and anatase TiO2 were uniformly deposited on surface of α-Fe2 O3 cores. Due to the heterojunction effects, α-Fe2 O3 @TiO2 NPs exhibited much stronger optical absorption in ultraviolet–visible (UV–Vis) district. For degradation of Rhodamine B (RhB), 3D flower-like α-Fe2 O3 @TiO2 NPs displayed much higher photocatalytic activity than that of pure α-Fe2 O3 and TiO2 NPs. Finally, the photocatalytic mechanism of α-Fe2 O3 @TiO2 NPs was proposed and explained. Highlights: Ellipsoidal α-Fe2 O3 @TiO2 nanoparticles was successfully prepared by modified Stöber method. The absorption of α-Fe2 O3 @TiO2 nanoparticles are enhanced in UV–Vis region and broadened in visible region. α-Fe2 O3 @TiO2 heterojunction exhibited excellent photocatalytic activity in degradation of RhB.